The Exchange Rate Susceptibility of Some European Core Industries and the Currency Union - David Leuwer; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper investigates the relationship between real exchange rate changes and the German, French and UK automobile and mechanical engineering sector. In stylized models, exports decline whenever the domestic currency appreciates and vice versa. Strategic firm behavior, however, can obscure the unambiguousness of this relationship, rendering the impact of a strengthening Euro on exports and on overall order volume unclear. To quantify the impact of the EUR/USD real exchange rate on German and French key exporting industries, we estimate a trivariate VAR based on monthly data from 1995 to 2010, respectively. We proceed analogously with the GBP/USD rate and the UK automobile and mechanical engineering sector series. Our findings indicate that an appreciating Euro hampers exports in the German and French core sectors, but does not cause these industries pain in the sense of an aggravated business climate. The latter does not apply to the respective time series for the UK. Time varying parameter VAR estimates confirm this immunization for members in the period after installation of the currency union.
Keywords: C30; E42; F41; 330; exporting sectors; confidence indicators; time varying parameter VAR